Investigating the effect of Staphylococcus epidermidis on the growth dynamics of Staphylococcus aureus in atopic dermatitis - Moonsamy, Rasalika Tamika (Department of Molecular and Cell Biology, 2025)
Background: In atopic dermatitis (AD), studies have demonstrated inconsistencies in the interactions between Staphylococcus epidermidis and Staphylococcus aureus concerning growth and biofilm formation outcomes. This suggests that there might be a strain-level role played by the bacteria that affect the outcomes of their interactions, and consequently, the pathophysiology of AD. Furthermore, the factors that mediate these effects by S. epidermidis, are currently poorly characterised. Objective: To evaluate the effect of skin and nasal S. epidermidis on the growth dynamics and biofilm formation of co-colonising S. aureus in toddlers with and without AD. Methods: Twenty-eight (28) previously identified co-colonising pairs of S. aureus and S. epidermidis isolates were selected based on different combinations of biofilm-forming strengths. Filtered S. epidermidis-derived supernatant was incubated with S. aureus cultures to determine its effect on biofilm formation and growth. Biofilm formation was evaluated using crystal violets assays and Alamar Blue assays were used to determine cell viability. S. aureus biofilms were treated with Proteinase K (PK) or sodium metaperiodate (SM) to determine their composition. The expression of extracellular serine protease (esp) was determined by Real Time Polymerise Chain Reaction (RT-PCR). S. epidermidis-derived supernatants subjected to heat, PK and SM to characterise other potential effector molecules. Lastly, sequence types (ST) and clonal complexes (CC) of S. epidermidis and S. aureus isolates were inferred from multi-locus sequence typing profiling. Results: Pairs of S. aureus and S. epidermidis from 75% (6/8) of controls and 65% (13/20) of cases demonstrated a decrease in biofilm formation compared with S. aureus alone. No significant differences in biofilm formation were noted between pairs isolated from cases and controls. From the viability assays, we observed that pairs of S. epidermidis and S. aureus from 25% of cases compared with 80% of pairs from controls had an increase in cell viability. The majority (70%) of established biofilms were composed of a proteinaceous matrix. Expression of esp was detected in 63% of S. epidermidis isolates. Heat-treated supernatant resulted in 50% of controls and 35% of case pairs displaying an increase in biofilm biomass. Incubation with SM-treated S. epidermidis supernatants resulted in 50% of isolates from control and case pairs showing decreases in biofilm iv biomass. Pairs from control (88%) and case (65%) participants treated with PK showed decreases in biofilm formation. Only five S. epidermidis isolates matched to exact STs, while several partially matched to several possible STs. The clonal lineages of the S. aureus control isolates were made up of CC1, CC5, and CC121, whereas the case isolates also included CC15 and CC8. Conclusions: The variation displayed in the biofilm formation results indicates S. epidermidis strain specificity plays a role in the outcome of interactions. Results from treated supernatant suggest the possibility of multiple effector molecules with different constituents. Lastly, S. aureus strains exhibit monoclonality whereas S. epidermidis strains present diverse strain compositions, which could be the basis for the differential outcomes observed. Future research should apply a holistic approach to microbiome studies to understand the different factors influencing the outcome of interactions leading to biofilm production